Implementation of Student Character Formation Through Islamic Religious Education - Mala Komalasari; Abu Bakar Yakubu (At-tadzkir: Islamic Education Journal, 2023)
This article aims to analyze character formation in PAI learning. The method of writing this article uses a literature study, namely by taking journal articles, books, and other sources for analysis. Character education is indeed a major issue in education. Apart from being part of the process of forming the morals of the nation's children, character education is expected to be the main foundation in increasing the degree and dignity of the Indonesian nation. Within the Ministry of National Education itself, character education is the focus of education at all levels of education it fosters. Islamic education is very important in shaping and developing students' character. Religious and moral education must integrate and interact with each other through the social reality that develops in society. Education that contains religious values is ultimately able to form a complete human being.